Review on Fossil records of the Kinta Valley Limestones - Haylay Tsegab, WA Hunter, Bernard J Pierson, WS Chow, . (2011)
Kinta valley was a focus of interest in search of geological resources for the last ten decades. Most of those studies were oriented to reveal the genesis of tin mineralization. Few workers including the current authors have identified some micro faunal (bivalves, gastropods, rugose corals, foraminifera, crinoids) records for relative dating of the limestone sequences.